"Influencia de la temperatura y la agitación del medio corrosivo constituido por hcl-0.5m y h2so4-0.5m, sobre la velocidad de corrosión del acero astm a335 grado p11, medido mediante diferentes técnicas electroquímicas” - Robles Valera, Marlon Elton (2015)
Low alloy steels are widely employed for boiler tubing and steam piping in thermal power plants. This is mainly due to its excellent oxidation and corrosion resistance as well its creep creep. Scale formation in internal surface of boiler tubes is one of the major problems in most of high pressure boilers. This causes two major problems: (1) Loss of heat transfer, and (2) Under-deposit corrosion. Therefore, it is necessary to clean, and mineral acids are typically employed for this purpose, always seeking to its corrosive effect is minimal with the parent material. In the present study, rates of corrosion of low alloy ASTM A335 grade P11 boiler steel were monitored in hydrochloric and sulphuric acid solutions at different temperatures (298–338 K) and stirring velocities (0 – 700 rpm), using methods: Tafel extrapolation, linear polarization resistance, electrochemical impedance spectroscopy and electrochemical frequency modulation. The relationship between the rate of corrosion on P11 steel and the temperature of the acid medium follow the Arrhenius kinetic model. The increase of the temperature and stirring of the acid solution produced on the surface of the P11 steel a depolarization of the reaction of hydrogen evolution, which contributes to the increase in the rate of corrosion. Also, the corrosion rate of P11 steel in H2SO4 -0.5M is much greater than in HCl-0.5M, for all temperatures evaluated.